Exploring the predictors affecting the sense of community of Korean high school students: application of random forests and SHAP - Jang, Eunah; Chung, Hyewon (Frontiers in Psychology, 2024)
Adolescence is a stage during which individuals develop social adaptability through meaningful interactions with others. During this period, students gradually expand their social networks outside the home, forming a sense of community. The aim of the current study was to explore the key predictors related to sense of community among Korean high school students and to develop supportive policies that enhance their sense of community. Accordingly, random forests and SHapley Additive exPlanations (SHAP) were applied to the 7th wave (11th graders) of the Korean Education Longitudinal Study 2013 data (n = 6,077). As a result, 6 predictors positively associated with sense of community were identified, including self-related variables, “multicultural acceptance,” “behavioral regulation strategy,” and “peer attachment,” consistent with previous findings. Newly derived variables that predict sense of community include “positive recognition of volunteering,” “creativity,” “observance of rules” and “class attitude,” which are also positively related to sense of community. The implications of these results and some suggestions for future research are also discussed.